2020
DOI: 10.1136/jnnp-2020-322924
|View full text |Cite
|
Sign up to set email alerts
|

Regional hyperperfusion in cognitively normalAPOE ε4allele carriers in mid-life: analysis of ASL pilot data from the PREVENT-Dementia cohort

Abstract: BackgroundRegional cerebral hypoperfusion is characteristic of Alzheimer’s disease (AD). Previous studies report conflicting findings in cognitively normal individuals at high risk of AD. Understanding early preclinical perfusion alterations may improve understanding of AD pathogenesis and lead to new biomarkers and treatment targets.Methods3T arterial spin labelling MRI scans from 162 participants in the PREVENT-Dementia cohort were analysed (cognitively normal participants aged 40–59, stratified by future de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Conflicting results have been reported on CBF changes in CU individuals with elevated risk of AD. While some studies have shown patterns of hyperperfusion in CU APOE ε4 carriers (Wierenga et al, 2014;McKiernan et al, 2020), others have found no CBF changes in CU individuals with Aβ pathology (Binnewijzend et al, 2016). Our findings endorse the latter indicating that ASL-CBF is a marker of the disease severity, not directly related to Aβ deposition.…”
Section: Discussionsupporting
confidence: 60%
“…Conflicting results have been reported on CBF changes in CU individuals with elevated risk of AD. While some studies have shown patterns of hyperperfusion in CU APOE ε4 carriers (Wierenga et al, 2014;McKiernan et al, 2020), others have found no CBF changes in CU individuals with Aβ pathology (Binnewijzend et al, 2016). Our findings endorse the latter indicating that ASL-CBF is a marker of the disease severity, not directly related to Aβ deposition.…”
Section: Discussionsupporting
confidence: 60%
“…Their association with cognitive performance in APOEe4 carriers was examined using longitudinal data from the PREVENT-Dementia study. Building on previous findings from our group, 37 our hypothesis was that we would observe evidence of hyper-perfusion and reduced CVRi in APOEe4 carriers at baseline. Furthermore, we hypothesised that significant interactions between hemodynamic measures and APOEe4 carriership in predicting cognitive scores would be recorded (positive for CBF and negative for CVRi for APOEe4 carriers), in line with our baseline compensatory perfusion hypothesis.…”
Section: Introductionmentioning
confidence: 70%
“…Our group’s previously reported findings from cognitively healthy middle-aged participants have related these three risk factors to a range of structural and functional brain changes, including APOE □4 genotype to loss of volume in the hippocampal molecular layer [17], and to cerebral hyperperfusion [18-19]; FH to volumetric alterations in hippocampal subfields and to disrupted white matter integrity [18, 20]; and, CAIDE to whole brain atrophy [21-23] and to hippocampal volume loss [20, 23]. APOE □4, FH and CAIDE have also been found to impact cognition in mid-life.…”
Section: Introductionmentioning
confidence: 99%